PENGARUH EKSPEKTASI KEGIATAN USAHA TERHADAP INDEKS HARGA SAHAM GABUNGAN (Studi Kasus pada Bursa Efek Indonesia) - Sumarsono Sumarsono; Safira Amalia Hapsari (Jurnal Manajemen Maranatha, 2018)
The stock price reflect the performance of the company issuing the shares, not only at running time (t0) but also expectations for the future (t+). The intrinsic value of the stock is investor’s income in the form of dividends which depends on the income from business activities, so rating for effect of expectations of business activities can be seen as a reflection of expectations and risks to the performance of the company issuing the shares  in the stock market which will affect stock prices, as reflected by Composite Stock Price Index (CSPI). This study aims to assess the effect of expectations of business activities on CSPI. The hypothesis is variables expectations of business activities individually or collectively affect the CSPI. Variable expectations of business activity expectation during the running time (t0) on business activity, financial condition and easiness access to credit and expectations in the future (t+) of business’s situation on three months ahead (t+3) and six months ahead (t+6). The study used survey data quarterly Kegiatan Dunia Usaha conducted by Bank Indonesia started from the first quarter of 2002 until the third quarter of 2016 and the data from Indonesia Stock Exchange Composite Stock Price Index after adjustment. Data taken from the publication of Bank Indonesia and Yahoo Finance. Hypothesis testing is using multiple regressionThe results of hypothesis testing found empirical evidence that the variable expectation of the company's financial condition of the present time and the expectation of business situation six months ahead have a significant positive effect on CSPI and business situation expectation over the next three months have a significant negative effect on CSPI. The variable of expectation of the current business activity and the expectation of easy access of credit have no significant effect to CSPI. All variable of expectation of business activity together have significant influence to CSPI. Keywords: Expectation of Business Activity, Composite Stock Price Index (CSPI).